USING PODCAST TO IMPROVE STUDENTS’ LISTENING COMPREHENSION ON DESCRIPTIVE TEXT - Mifta Danu Prasetyo; Machdalena Vianty; Hariswan Putra Jaya (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2014)
Abstract: The objective of the study was to find out whether or not the use of Podcast significantly improved students’ listening comprehension on descriptive text. The population of the study was the eighth grade students of SMP Negeri 10 Palembang in the academic year 2013/2014. The sample was 40 students that were taken by using a population single technique. This study applied pre-experimental research method, which was, one group pre-test post-test design. The data were collected by means of a listening test. The result of the paired sample t-test showed that the mean difference between students’ pre-test and post-test was 22.57, with significance value was .000. This result showed that teaching listening comprehension through Podcast had a significant effect on students’ listening comprehension. In other words, it can be concluded that teaching listening comprehension through Podcast significantly increased students’ listening comprehension. Key words: listening comprehension, Podcast, descriptive text